Key Factors in Home Buying Decisions Quality, Price, and Location: Faktor Kunci dalam Keputusan Membeli Rumah Kualitas, Harga, dan Lokasi - Ependi, Moch.Zaenal; Oetarjo, Msa (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the impact of product quality, price, and location on home buying decisions in Bumi Papan Selaras Housing, Sidoarjo, Indonesia. Utilizing a quantitative survey method with 96 respondents, the research analyzes data using various statistical tests in SPSS version 26. Results reveal that product quality, price, and location significantly influence home purchasing choices both individually and collectively. These findings underscore the importance of considering multiple factors simultaneously in housing market dynamics, aiding developers and policymakers in catering to consumer preferences effectively and promoting sustainable urban development. Highlight: Comprehensive Study: Investigates multifactor influence on home purchases. Consumer Preferences: Analyzes product quality, price, and location significance. Methodological Rigor: Employs survey method for accurate data collection. Keywoard: Home Buying Decisions, Product Quality, Price, Location, Survey Method